Education achievements in urban schools in Peru - Soto Quiroga, Patricia (2011)
This dissertation, primarily, evaluates the extent at which some family characteristics and school characteristics affect students’ achievement in Peru. For this purpose, the data used in this study is based on a survey conducted in Peru in 2009, to 3,438 students of 60 schools in 17 urban cities in the country. Finally, as we can see, the role of the government to close the inequality gaps in schools is decisive, as those gaps have a multiplicative effect in the wage gap when students from poorer backgrounds enter the labour market.